Comparison Of Sleep Hygiene Index In Virtual, Textbook And Hybrid Learners In Undergraduate Students - Hania Latif Sami; Syeda Fatemah Raza Zaidi; Mian Ahmed Haroon; Ata Ul Haiy (International Journal of Medical Students)
BACKGROUND: Sleep hygiene is a set of behavioral and environmental factors that promote healthy sleep (1). The digital age has changed the way we learn by incorporating technology with textbooks. Screens emitting blue light suppress melatonin release and alter the Circadian rhythm, leading to an irregular sleep-wake cycle and poor sleep quality, which can be measured by sleep hygiene (2-9). Healthcare students are at an increased risk of developing poor sleep hygiene due to their long study and clinical hours. This study explores the relationship between different learning modes (textbook, virtual, and hybrid) and sleep hygiene among students at Shalamar Institute of Health Sciences.